Faktor Munculnya Gejala Stres pada Mahasiswa secara Global Akibat Pembelajaran Jarak Jauh di Masa Pandemi Covid-19 - Andi Badli Rompegading; Muh. Fathir Rahmat; Rizal Irfandi; Cindy Agustina; Dian Ramadhani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the variable emergence of side effects of pressure on students globally due to distance traveled during the Coronavirus pandemic. The method used is literature (meta-analysis) by reviewing articles that discuss indications of stress (stress) in college students globally. The results showed that the emergence of symptoms of pressure on students was caused by distance and piling up of coursework, learning environment, noise, limited understanding of the material obtained, limited knowledge, piled up homework, not having the option to meet friends and family including schoolmates, forced internet networks, inefficient web standards, no proper class plans, unstable internet networks, relatively expensive data costs and fatigue experienced during distance learning. As a result, students experience stress during the COVID-19 pandemic. In conclusion, students globally experience stress due to several factors arising from distance learning during the COVID-19 pandemic. Keywords: COVID-19, Symptoms of stress, Distance learning